Analysis Of Policy Implementation In Tanjungpinang Flood Disaster Risk Reduction - Lamidi Lamidi (Al-Makki Publisher, 2022)
Disaster management is an early awareness to reduce the risk of potential disasters, especially floods in the community. This study aims to analyze implementing policies in Tanjungpinang Flood Disaster Risk Reduction. The research object was chosen because Tanjungpinang, on a land geographical location, is smaller than the sea area and can potentially be a disaster threat in an archipelagic area. Analysis of Policy implementation using Edward III Model. The research method is descriptive qualitative with a case study approach—the data obtained using secondary data with analysis of relevant training techniques. The study results indicate that four factors in the Edward III model have several weaknesses in the Tanjungpinang Flood Disaster Risk Reduction findings. The factors in question are the lack of cooperation in the bureaucratic structure on a large scale. The resources used have not met the standardization with the minimal involvement of resources in improving the quality of both technical and non-technical. Communication still has a good intensity between the stakeholders involved, so the participating actors are still running fast following the flood disaster management program in Tanjungpinang City. Furthermore, lastly, the attitude of the implementer or disposition has their respective ego-sectoral so that the participation between stakeholders in its implementation is less effective. Researchers provide additional recommendations or alternatives that need to strengthen policy implementation with a community empowerment approach so that people gain insight into disaster awareness involved in disaster management programs, primarily floods in Tanjungpinang City, for the future on a sustainable basis.